1990
DOI: 10.1002/bjs.1800770324
|View full text |Cite
|
Sign up to set email alerts
|

Indications for conservative management of acute scrotal pain in children

Abstract: Forty-three boys who presented with acute scrotal pain were studied retrospectively. Of these, 40 had torsion of scrotal contents. Torsion of testicular appendages, a self limiting condition, tended to present later than testicular torsion (P = 0.002). The testis was saved in all 11 cases of testicular torsion explored within 12h of the onset of pain but orchidectomy was required in four who presented later. In 11 cases, a torted testicular appendage diagnosed as a tender nodule was found on examining the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…Scrotal tenderness, the position or lie of the testis, the presence of a blue dot, hydrocoeles, the cremasteric reflex and erythema are reported as useful signs [6]. Different centres place varying emphasis on each of these factors [7][8][9]. However, we found that clinical signs were not absolute.…”
Section: Discussionmentioning
confidence: 74%
“…Scrotal tenderness, the position or lie of the testis, the presence of a blue dot, hydrocoeles, the cremasteric reflex and erythema are reported as useful signs [6]. Different centres place varying emphasis on each of these factors [7][8][9]. However, we found that clinical signs were not absolute.…”
Section: Discussionmentioning
confidence: 74%
“…The transverse elevated lie of the testis described in testicular torsion [5] was observed in only 4 (36.4%) patients in our study, and in 46% by Kadish and Bolte [11] . Early cases of torsion of testicular appendage may be distinguished by the localized polar tenderness and by the blue dot sign which have been reported in around 40% of patients [2,5,6] ; this sign contributed to the diagnosis in 1 of our patients. However when the presentation is beyond 24 h, there is often generalized swelling and tenderness making the condition diffi cult to diagnose clinically [6] .…”
Section: Discussionmentioning
confidence: 97%
“…Early cases of torsion of testicular appendage may be distinguished by the localized polar tenderness and by the blue dot sign which have been reported in around 40% of patients [2,5,6] ; this sign contributed to the diagnosis in 1 of our patients. However when the presentation is beyond 24 h, there is often generalized swelling and tenderness making the condition diffi cult to diagnose clinically [6] . Leukocytosis and pyuria have been reported to occur in around two thirds of patients with epididymitis [9], but is occasionally observed in some patients with testicular torsion [2,11] .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations